2022
DOI: 10.3390/children9101445
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3D Printed Resin Crowns for Primary Molars: In Vitro Study of Fracture Resistance, Biaxial Flexural Strength, and Dynamic Mechanical Analysis

Abstract: This study evaluated the fracture resistance, biaxial flexural strength (BFS), and dynamic mechanical analysis (DMA) of three-dimensional (3D) printing resins for the esthetic restoration of primary molars. Two 3D printing resins, Graphy (GP) and NextDent (NXT), and a prefabricated zirconia crown, NuSmile (NS), were tested. GP and NXT samples were 3D printed using the workflow recommended by each manufacturer. Data were collected and statistically analyzed. As a result of the fracture resistance test of 0.7-mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 27 publications
2
18
0
1
Order By: Relevance
“…Two important findings deserving further discussion emerged from this study: the results indicated a clinical equivalence between the fracture resistance of the different 3D-printed test specimens, and the mean value of the forces required to fracture the sample crowns was shown to exceed 2000 N. The latter finding aligns with previous research into the fracture resistance of 3D-printed reinforced resin crowns: forces between 1495.05 and 2303.7 N were recorded for tests on teeth located in the back of the mouth [12,46]. This is significant as it exceeds the average human bite force, which has been shown to increase with age: humans aged 6-8 years exert a force of 78 N rising to a maximum of 176 N at ages 18-20 years [47].…”
Section: Discussionsupporting
confidence: 86%
“…Two important findings deserving further discussion emerged from this study: the results indicated a clinical equivalence between the fracture resistance of the different 3D-printed test specimens, and the mean value of the forces required to fracture the sample crowns was shown to exceed 2000 N. The latter finding aligns with previous research into the fracture resistance of 3D-printed reinforced resin crowns: forces between 1495.05 and 2303.7 N were recorded for tests on teeth located in the back of the mouth [12,46]. This is significant as it exceeds the average human bite force, which has been shown to increase with age: humans aged 6-8 years exert a force of 78 N rising to a maximum of 176 N at ages 18-20 years [47].…”
Section: Discussionsupporting
confidence: 86%
“…A previous paper described the fillers as phosphine oxides. 7 Several of the fillers also have ytterbium added for radiopacity. The milled and conventional resin composite contained clusters of silica and zirconia, which are unique for this brand of resin composite.…”
Section: Discussionmentioning
confidence: 99%
“…C&B MFH also contained 1–2‐μm flakes that may be an oxide of silicon, aluminum, or titanium with a carbon‐containing organic component. A previous paper described the fillers as phosphine oxides 7 . Several of the fillers also have ytterbium added for radiopacity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations